The Effectiveness of Judo Techniques in Real-World Self-Defence Situations - Verma, Arun; Munder, Suneel (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Judo, a martial art established in Japan by Jigoro Kano, prioritizes leverage, balance, and technique over brute force. As society continues to face increasing concerns regarding personal safety, this study examines Judo’s effectiveness as a self-defence system in contemporary, unpredictable, and often violent real-world contexts. Through a combination of historical analysis, technical review, expert commentary, and real-life case studies, this paper aims to identify the strengths, limitations, and situational adaptability of Judo techniques. The research also considers the psychological conditioning instilled by Judo and discusses its integration with other martial systems for holistic personal defence.